Mutation Load of Single, Large-Scale Deletions of mtDNA in Mitotic and Postmitotic Tissues - Jeppesen, Tina D.; Duno, Morten; Vissing, John (Frontiers in Genetics, 2020)
It is generally accepted that patients with chronic progressive ophthalmoplegia caused by single large-scale deletion of mtDNA only harbor mutation in skeletal and eye muscles. The aim of this study was to investigate the presence and the level of heteroplasmy of mtDNA deletions in mitotic tissues of patients displaying mtDNA deletion of mitotic tissues in patients with single, large-scale deletions and pure muscle phenotype. MtDNA mutation load was studied in three mitotic (urine epithelial cells, buccal mucosa and blood) and one post-mitotic (skeletal muscle) tissues in 17 patients with single, large-scale deletions of mtDNA and pure muscle involvement. All patients had mtDNA deletion in skeletal muscle and 78% of the patients also displayed the mtDNA deletion in mitotic tissues. The mtDNA mutation load was higher in skeletal muscle vs. mitotic tissues. The mtDNA mutation load did not correlate with age of sampling of tissues, but there was a correlation between the mtDNA mutations load in skeletal muscle and 1) the site of 5’end breaking point of the SLD, 2) the size of SLD, 3) the number of affected tRNAs, and 4) age at onset (r > 0.58; P < 0.05). The findings indicate that mtDNA mutation in mitotic tissue is common in patients with single, large-scale deletions of mtDNA. The lack of correlation between age of tissue sampling, age at onset and mtDNA mutation load in mitotic tissues, indicate, that there is no extensive post-natal modification of mtDNA mutation load in mitotic tissues of patients with pure muscle phenotype.